Data Adaptive Spectral Analysis of Unsteady Leakage Flow in an Axial Turbine - Konstantinos G. Barmpalias; Ndaona Chokani; Anestis I. Kalfas; Reza S. Abhari (International Journal of Rotating Machinery)
A data adaptive spectral analysis method is applied to characterize the unsteady loss generation in the leakage flow of an axial turbine. Unlike conventional spectral analysis, this method adapts a model dataset to the actual data. The method is illustrated from the analysis of the unsteady wall pressures in the labyrinth seal of an axial turbine. Spectra from the method are shown to be in good agreement with conventional spectral estimates. Furthermore, the spectra using the method are obtained with data records that are 16 times shorter than for conventional spectral analysis, indicating that the unsteady processes in turbomachines can be studied with substantially shorter measurement schedules than is presently the norm.